An electrolyte for electrochemical forming of amorphous alloy materials and preparation method thereof
By preparing an electrolyte containing ferric chloride, nickel chloride, hydrogen peroxide, graphene quantum dots, ethylene glycol and ethanol, the problem that existing electrolyte cannot achieve high-quality and efficient forming in the electrochemical forming of amorphous alloys is solved, and higher processing accuracy, efficiency and yield are achieved, reducing costs and short-circuit risks.
Patent Information
- Application Number
- CN202310132170.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-02-20
AI Technical Summary
The existing electrolyte cannot achieve high-quality and efficient forming during the electrochemical forming process of amorphous alloy materials, and there are many processing products, large volumes, and strong adhesion, which are prone to short circuits and affect the production process.
提供一种用于非晶合金材料电化学成形的电解液,其成分包括氯化铁、氯化镍、过氧化氢、石墨烯量子点、乙二醇和乙醇,通过特定的混合和搅拌步骤制备,调整pH值为5.5-6.8。
This electrolyte is suitable for electrochemical forming processing of most amorphous alloy materials, improving processing accuracy and efficiency, reducing surface roughness and short circuit risks, improving yield, and reducing the preparation cost of the electrolyte.
Smart Images

Figure CN116079166B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material processing engineering, and in particular relates to an electrolyte for electrochemical forming of amorphous alloy materials and a preparation method thereof. Background Art
[0002] Amorphous alloys are new alloy materials made by modern ultra-rapid solidification metallurgical technology, which have excellent mechanical, physical and chemical properties of general metals and glasses. The internal atomic arrangement is a glassy structure with short-range order and long-range disorder. It is in a metastable state in energy, without the grains and grain boundaries of crystalline alloys, and the structure and composition are more uniform than crystalline alloys. Amorphous alloys provide excellent materials for the miniaturization and precision of high-tech products, and can overcome the shortcomings of macroscopic brittleness and fully demonstrate the superior performance of its materials at a small scale. Therefore, amorphous alloys are more suitable for use as parts materials for precision / ultra-precision forming. At the same time, amorphous alloys have the characteristics of high strength, corrosion resistance, and good molding finish. The precision parts manufactured do not need additional surface strengthening and hardening treatment processes, and have better application prospects. Existing micro-manufacturing technologies (for example, micro-milling, micro-electric spark, micro-laser, etc.) will generate high temperatures and certain stresses during the processing process, which can easily cause the amorphous structure of metallic glass to transform into a crystalline state, reducing the excellent performance of the material itself. Micro-electrolytic machining is usually carried out in an electrolyte at room temperature. It does not produce machining stress and does not cause material crystallization, fully ensuring the excellent performance of the material itself.
[0003] Electrochemical forming technology generally uses metal sheets or wires with specific morphologies as tools, combined with high-precision multi-axis CNC motion, and is a method of profiling metal materials based on the principle of electrochemical anodic dissolution. Compared with other processing technologies, electrochemical forming technology has the characteristics of no tool loss, no stress on the processing surface, no metamorphic layer, and no relation to the hardness of the part material. Combined with ultra-short pulse power supply, the processing accuracy has reached sub-micron level. Moreover, electrochemical forming technology belongs to "cold" and "non-contact" manufacturing technology, with low processing temperature and no stress, and will not affect the amorphous structure during the processing process. Therefore, electrochemical forming technology is an ideal technical means to manufacture precision parts of amorphous alloys.
[0004] However, the electrolytes commonly used at home and abroad are usually pure water and acid, alkali, and salt as the main components, and are usually used for crystalline alloy materials. Studies have shown that when the electrolyte used for traditional crystalline alloys is used for amorphous alloys, an oxide layer (passivation film) will be produced on the surface of the amorphous alloy, which hinders the rapid processing of the material, and can only produce a trace amount of surface corrosion, and high-quality rapid processing cannot be achieved. At the same time, due to the complex composition of amorphous alloys, there are many processed products in the electrolyte with pure water and acid, alkali, and salt as the main components, which are large in volume, strong in adhesion, and prone to short circuits, which have an adverse effect on the production process, and the surface quality of the processed parts is poor. After investigation, there is no electrolyte specifically used for rapid electrochemical forming of amorphous alloys in China. Therefore, the development of a suitable electrolyte is of great significance to improving the stability and surface quality of electrochemical forming of amorphous alloys. Summary of the invention
[0005] The object of the present invention is to provide an electrolyte and a preparation method for electrochemical forming of amorphous alloy materials, so as to solve the problems existing in the prior art.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: an electrolyte for electrochemical forming of amorphous alloy materials, comprising 5%-15% ferric chloride, 5%-10% nickel chloride, 5%-15% hydrogen peroxide, 2%-10% graphene quantum dots, 8%-22% ethylene glycol, and 26%-74% ethanol, wherein the percentages of the compounds are by weight and the remainder is a pH regulator.
[0007] Preferably, ferric chloride 5%, nickel chloride 5%, hydrogen peroxide 5%, graphene quantum dots 2%, ethylene glycol 8%, ethanol 74%, and the remainder pH adjuster.
[0008] Preferably, 15% ferric chloride, 10% nickel chloride, 15% hydrogen peroxide, 10% graphene quantum dots, 22% ethylene glycol, 26% ethanol, and the remainder pH adjuster.
[0009] A method for preparing the electrolyte for electrochemical forming of amorphous alloy materials comprises the following steps:
[0010] Step 1: In a temperature control box, ferric chloride, nickel chloride and ethylene glycol are mixed according to weight percentage, and stirred evenly to obtain a mixed solution;
[0011] Step 2: In a temperature-controlled box, add ethanol according to the weight percentage to the mixed solution obtained in step 1 and continue stirring;
[0012] Step 3: In a temperature-controlled box, add graphene quantum dots according to weight percentage to the solution obtained in step 2, and continue stirring;
[0013] Step 4: In a temperature-controlled box, add the remaining pH adjuster to the solution obtained in step 3 until the pH value is 5.5-6.8, and continue stirring until the electrolyte is prepared.
[0014] Preferably, in step 1, the temperature of the temperature control box is 30-50° C., the stirring rate is 120-180 r / min, the time is 5-10 min, and ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 150-200 KHz.
[0015] Preferably, in step 2, the temperature of the temperature control box is 25-30° C., the stirring rate is 100-120 r / min, the time is 5-10 min, and ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 100-150 KHz.
[0016] Preferably, in step 3, the temperature of the temperature control box is 20-25° C., the stirring rate is 60-100 r / min, the time is 5-10 min, and ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 80-100 KHz.
[0017] Preferably, in step 4, the temperature of the temperature control box is 20° C., the stirring rate is 30-60 r / min, the time is 5-10 min, and ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 80-100 KHz.
[0018] Preferably, in step 4, after the preparation of the electrolyte is completed, under the working condition of 20° C., the conductivity of the electrolyte needs to be controlled to be 5-100 mS / cm before it can be put into electrochemical forming processing.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention relates to an electrolyte for electrochemical forming of amorphous alloy materials, which is suitable for the electrochemical forming processing of most commonly used amorphous alloy materials, has high precision control and processing efficiency, high yield, low processing surface roughness and good surface quality, and solves the problem that the existing electrolyte with pure water and acid, alkali and salt as main components cannot achieve high-quality and high-efficiency forming of amorphous alloy materials, and the problem that in traditional electrolytes, there are many processed products in the electrochemical forming process, the volume is large, the adhesion is strong, and short circuits are easy to occur.
[0021] The present invention relates to a method for preparing an electrolyte for electrochemical forming of an amorphous alloy material. The cost of generating the electrolyte for electrochemical forming of an amorphous alloy material is low, and the entire preparation operation is simple. Since no toxic substances with a large impact on the environment are produced, the impact on the environment is small. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1It is a schematic diagram of the electrochemical forming processing state of the amorphous alloy involved in the present invention;
[0023] Figure 2 This is a measurement diagram of the surface roughness of an amorphous alloy after electrochemical forming in Example 1;
[0024] Figure 3 This is a measurement diagram of the surface roughness of the amorphous alloy after electrochemical forming in Example 2;
[0025] Figure 4 This is a measurement diagram of the surface roughness of the amorphous alloy after electrochemical forming in Example 3;
[0026] Figure 5 This is a measurement diagram of the surface roughness of the amorphous alloy after electrochemical forming in Example 4;
[0027] Figure 6 This is a measurement diagram of the surface roughness of the amorphous alloy after electrochemical forming in Example 5. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0029] Preface:
[0030] See also Figure 1 The electrolyte for electrochemical forming of amorphous alloy materials disclosed in the present invention is connected to the amorphous alloy material with the positive electrode of the power supply, and the conductive wire with the negative electrode, and the prepared electrolyte is poured into the electrolyte tank to immerse the conductive wire and the amorphous alloy material. By utilizing the principle of electrochemical anode dissolution and forming the amorphous alloy material through the numerical control movement of the conductive wire, precision parts with large aspect ratio and complex shapes can be manufactured. The parameters of the power supply in the following embodiments remain the same.
[0031] An electrolyte for electrochemical forming of amorphous alloy materials, comprising 5%-15% ferric chloride (FeCl3), 5%-10% nickel chloride (NiCl3), 5%-15% hydrogen peroxide (H2O2), 2%-10% quantum dots (GQD), 8%-22% ethylene glycol ((CH2OH)2), and 26%-74% ethanol (C2H5OH), wherein the percentages of the compounds are weight percentages and the remainder is a pH regulator.
[0032] A method for preparing an electrolyte for electrochemical forming of an amorphous alloy material comprises the following steps:
[0033] Step 1: In a temperature control box, add ferric chloride, nickel chloride and ethylene glycol according to weight percentage, mix, and stir evenly to obtain a mixed solution;
[0034] Step 2: In a temperature-controlled box, add ethanol according to the weight percentage to the solution obtained in step 1 and continue stirring;
[0035] Step 3: In a temperature-controlled box, add quantum dots according to weight percentage to the solution obtained in step 2 and continue stirring;
[0036] Step 4: In a temperature-controlled box, add the remaining pH adjuster to the solution obtained in step 3 until the pH value is 5.5-6.8, and continue stirring until the electrolyte is prepared.
[0037] In step 1, the temperature of the temperature control box is 30-50°C, the stirring rate is 120-180r / min, the time is 5-10min, and ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 150-200KHz;
[0038] In step 2, the temperature of the temperature control box is 25-30° C., the stirring rate is 100-120 r / min, and the time is 5-10 min. At the same time, ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 100-150 KHz.
[0039] In step 3, the temperature of the temperature control box is 20-25° C., the stirring rate is 60-100 r / min, and the time is 5-10 min. At the same time, ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 80-100 KHz.
[0040] In step 4, the temperature of the temperature control box is 20° C., the stirring rate is 30-60 r / min, and the time is 5-10 min. At the same time, ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 80-100 KHz.
[0041] In step 4, after the electrolyte is prepared, under the working condition of 20°C, the conductivity of the electrolyte must be controlled to be 5-100mS / cm before it can be put into electrochemical forming processing.
[0042] The effects and properties of each component in the electrolyte are shown in Table 1:
[0043] Table 1
[0044]
[0045]
[0046] The following are Embodiment 1, Embodiment 2, Embodiment 3 and Embodiment 4 made in response to the above, and Embodiment 5 made based on the current conventional electrolyte.
[0047] Among them, ferric chloride is selected from industrial ferric chloride particles, nickel chloride is selected from industrial nickel chloride particles, hydrogen peroxide is selected from industrial concentration 30% hydrogen peroxide solution, graphene quantum dots are selected from industrial mass fraction 95% graphene quantum dot powder, ethylene glycol is selected from industrial purity 99%, ethanol is selected from industrial purity 99% ethanol, and the pH adjuster is selected from 37% (w / w) hydrochloric acid solution.
[0048] Embodiment 1:
[0049] An electrolyte for electrochemical forming of amorphous alloy materials comprises 5% ferric chloride, 5% nickel chloride, 5% hydrogen peroxide, 2% graphene quantum dots, 8% ethylene glycol and 74% ethanol, wherein the percentage of the compounds is weight percentage and the balance is a pH regulator, and the pH value of the electrolyte is 6.0.
[0050] A method for preparing an electrolyte for electrochemical forming of an amorphous alloy material comprises the following steps:
[0051] Step 1: In a temperature control box, add ferric chloride, nickel chloride and ethylene glycol according to weight percentage, mix, and stir evenly to obtain a mixed solution;
[0052] Step 2: In a temperature-controlled box, add ethanol according to the weight percentage to the solution obtained in step 1 and continue stirring;
[0053] Step 3: In a temperature-controlled box, add quantum dots according to weight percentage to the solution obtained in step 2 and continue stirring;
[0054] Step 4: In a temperature control box, add the remaining pH adjuster to the solution obtained in step 3, and continue stirring until the electrolyte is prepared.
[0055] In step 1, the temperature of the temperature control box is 30°C, the stirring rate is 120r / min, the time is 5min, and the ultrasonic coupling vibration frequency is 150KHz;
[0056] In step 2, the temperature of the temperature control box is 25°C, the stirring rate is 100 r / min, the time is 5 min, and the ultrasonic coupling vibration frequency is 100 KHz;
[0057] In step 3, the temperature of the temperature control box is 20°C, the stirring rate is 60r / min, the time is 5min, and the ultrasonic coupling vibration frequency is 80KHz;
[0058] In step 4, the temperature of the temperature control box is 20°C, the stirring rate is 30r / min, the time is 5min, and the ultrasonic coupling vibration frequency is 80KHz;
[0059] In step 4, after the electrolyte is prepared, the conductivity of the electrolyte is 25 mS / cm at 20°C.
[0060] Embodiment 2:
[0061] An electrolyte for electrochemical forming of amorphous alloy materials comprises 5% ferric chloride, 5% nickel chloride, 5% hydrogen peroxide, 2% graphene quantum dots, 8% ethylene glycol and 74% ethanol, wherein the percentage of the compounds is weight percentage and the balance is a pH regulator, and the pH value of the electrolyte is 6.0.
[0062] A method for preparing an electrolyte for electrochemical forming of an amorphous alloy material comprises the following steps:
[0063] Step 1: In a temperature control box, add ferric chloride, nickel chloride and ethylene glycol according to weight percentage, mix, and stir evenly to obtain a mixed solution;
[0064] Step 2: In a temperature-controlled box, add ethanol according to the weight percentage to the solution obtained in step 1 and continue stirring;
[0065] Step 3: In a temperature-controlled box, add quantum dots according to weight percentage to the solution obtained in step 2 and continue stirring;
[0066] Step 4: In a temperature control box, add the remaining pH adjuster to the solution obtained in step 3, and continue stirring until the electrolyte is prepared.
[0067] In step 1, the temperature of the temperature control box is 50°C, the stirring rate is 180r / min, the time is 10min, and the ultrasonic coupling vibration frequency is 200KHz;
[0068] In step 2, the temperature of the temperature control box is 30°C, the stirring rate is 120r / min, the time is 10min, and the ultrasonic coupling vibration frequency is 150KHz;
[0069] In step 3, the temperature of the temperature control box is 25°C, the stirring rate is 100 r / min, the time is 10 min, and the ultrasonic coupling vibration frequency is 100 KHz;
[0070] In step 4, the temperature of the temperature control box is 20°C, the stirring rate is 60r / min, the time is 10min, and the ultrasonic coupling vibration frequency is 100KHz;
[0071] In step 4, after the electrolyte is prepared, the conductivity of the electrolyte is 60 mS / cm at 20°C.
[0072] Embodiment three:
[0073] An electrolyte for electrochemical forming of amorphous alloy materials comprises 5% ferric chloride, 10% nickel chloride, 15% hydrogen peroxide, 10% graphene quantum dots, 22% ethylene glycol, and 26% ethanol, wherein the percentage of the compounds is weight percentage, the balance is a pH regulator, and the pH value of the electrolyte is 6.0.
[0074] A method for preparing an electrolyte for electrochemical forming of an amorphous alloy material comprises the following steps:
[0075] Step 1: In a temperature control box, add ferric chloride, nickel chloride and ethylene glycol according to weight percentage, mix, and stir evenly to obtain a mixed solution;
[0076] Step 2: In a temperature-controlled box, add ethanol according to the weight percentage to the solution obtained in step 1 and continue stirring;
[0077] Step 3: In a temperature-controlled box, add quantum dots according to weight percentage to the solution obtained in step 2 and continue stirring;
[0078] Step 4: In a temperature control box, add the remaining pH adjuster to the solution obtained in step 3, and continue stirring until the electrolyte is prepared.
[0079] In step 1, the temperature of the temperature control box is 30°C, the stirring rate is 120r / min, the time is 5min, and the ultrasonic coupling vibration frequency is 150KHz;
[0080] In step 2, the temperature of the temperature control box is 25°C, the stirring rate is 100 r / min, the time is 5 min, and the ultrasonic coupling vibration frequency is 100 KHz;
[0081] In step 3, the temperature of the temperature control box is 20°C, the stirring rate is 60r / min, the time is 5min, and the ultrasonic coupling vibration frequency is 80KHz;
[0082] In step 4, the temperature of the temperature control box is 20°C, the stirring rate is 30r / min, the time is 5min, and the ultrasonic coupling vibration frequency is 80KHz;
[0083] In step 4, after the electrolyte is prepared, the conductivity of the electrolyte is 40 mS / cm at 20°C.
[0084] Embodiment 4:
[0085] An electrolyte for electrochemical forming of amorphous alloy materials comprises 15% ferric chloride, 10% nickel chloride, 15% hydrogen peroxide, 10% graphene quantum dots, 22% ethylene glycol and 28% ethanol, wherein the percentage of the compounds is weight percentage and the balance is a pH regulator, and the pH value of the electrolyte is 6.0.
[0086] A method for preparing an electrolyte for electrochemical forming of an amorphous alloy material comprises the following steps:
[0087] Step 1: In a temperature control box, add ferric chloride, nickel chloride and ethylene glycol according to weight percentage, mix, and stir evenly to obtain a mixed solution;
[0088] Step 2: In a temperature-controlled box, add ethanol according to the weight percentage to the solution obtained in step 1 and continue stirring;
[0089] Step 3: In a temperature-controlled box, add quantum dots according to weight percentage to the solution obtained in step 2 and continue stirring;
[0090] Step 4: In a temperature control box, add the remaining pH adjuster to the solution obtained in step 3, and continue stirring until the electrolyte is prepared.
[0091] In step 1, the temperature of the temperature control box is 50°C, the stirring rate is 180r / min, the time is 10min, and the ultrasonic coupling vibration frequency is 200KHz;
[0092] In step 2, the temperature of the temperature control box is 30°C, the stirring rate is 120r / min, the time is 10min, and the ultrasonic coupling vibration frequency is 150KHz;
[0093] In step 3, the temperature of the temperature control box is 25°C, the stirring rate is 100 r / min, the time is 10 min, and the ultrasonic coupling vibration frequency is 100 KHz;
[0094] In step 4, the temperature of the temperature control box is 20°C, the stirring rate is 60r / min, the time is 10min, and the ultrasonic coupling vibration frequency is 100KHz;
[0095] In step 4, after the electrolyte is prepared, the conductivity of the electrolyte is 90 mS / cm at 20°C.
[0096] Embodiment five:
[0097] The conventional electrolyte contains inorganic salts and chelating agents (reference patent document: electrolyte for electrochemical processing and electrochemical processing method using the electrolyte, patent number: ZL201410217873.8), and a NaNO3 aqueous solution containing the disodium salt of 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP-2Na) is used as the electrolyte. The electrolyte contains 20% NaNO3, an inorganic salt, and 5% HEDP disodium salt, a chelating agent, and the pH value is guaranteed to be 6.0 during configuration.
[0098] Comparative experiment:
[0099] Preliminary preparation:
[0100] Prepare appropriate amounts of electrolytes of various proportions in the five embodiments, select amorphous alloy processing materials as amorphous alloy blocks, the size of which is 20CM*15CM*5CM (length*width*height), and prepare 100 amorphous alloy blocks of this specification in each embodiment, wherein 25 Ni-based amorphous alloy blocks, 20 Fe-based amorphous alloy blocks, 15 Cu-based amorphous alloy blocks, 8 Zr-based amorphous alloy blocks, 12 Mg-based amorphous alloy blocks, 6 Al-based amorphous alloy blocks, and 14 Zn-based amorphous alloy blocks are arranged from front to back for processing, prepare five CNC electrolytic processing equipment of the same model and the same debugging wiring data, and install conductive wires of the same specifications for standby use;
[0101] Process preparation:
[0102] Prepare the testing equipment, and enter the measuring process after processing each amorphous alloy block, including micrometer and roughness tester.
[0103] It was used for the electrochemical forming of the amorphous alloy material introduced in the previous section, and the experimental data were recorded. The finished product was judged as follows: the processing size error was not higher than 5%, and the surface roughness after processing was not higher than 1μm.
[0104] The results of the five embodiments are compared, as shown in Table 2.
[0105] Table 2
[0106]
[0107] It can be seen from the test results in Table 2 that, compared with Example 5, after using the electrolyte of the present invention, the processing efficiency, dimensional accuracy and yield rate (up to 100%) of electrochemical forming are significantly improved; at the same time, the surface roughness and electrode loss rate caused by short circuit are significantly reduced. Figure 2-6 It can be seen that the quality of the machined surface is significantly improved. In addition, the unit cost of preparing the electrolyte is significantly reduced.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.
Claims
1. An electrolyte for electrochemical forming of amorphous alloy materials, characterized in that: 5%-15% of ferric chloride, 5%-10% of nickel chloride, 5%-15% of hydrogen peroxide, 2%-10% of graphene quantum dots, 8%-22% of ethylene glycol, and 26%-74% of ethanol. The percentage of the compounds is weight percentage, and the balance is a pH regulator. Hydrogen peroxide is a 30% industrial concentration hydrogen peroxide solution, ferric chloride is industrial ferric chloride particles, nickel chloride is industrial nickel chloride particles, graphene quantum dots are graphene quantum dot powders with an industrial mass fraction of 95%, ethylene glycol is 99% industrial purity, and ethanol is 99% industrial purity ethanol. The balance of the pH regulator is added to a pH value of 5.5-6.8, and the pH regulator is a 37% (w / w) hydrochloric acid solution.
2. The electrolyte for electrochemical forming of amorphous alloy materials according to claim 1, characterized in that: Ferric chloride 5%, nickel chloride 5%, hydrogen peroxide 5%, graphene quantum dots 2%, ethylene glycol 8%, ethanol 74%, the balance pH regulator.
3. The electrolyte for electrochemical forming of amorphous alloy materials according to claim 1, characterized in that: Ferric chloride 15%, nickel chloride 10%, hydrogen peroxide 15%, graphene quantum dots 10%, ethylene glycol 22%, ethanol 26%, pH regulator balance 4. A method for preparing an electrolyte for electrochemical forming of amorphous alloy materials according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: In a temperature control box, ferric chloride, nickel chloride and ethylene glycol are mixed according to weight percentage, and stirred evenly to obtain a mixed solution; Step 2: In a temperature-controlled box, add ethanol according to the weight percentage to the mixed solution obtained in step 1 and continue stirring; Step 3: In a temperature-controlled box, add graphene quantum dots according to weight percentage to the solution obtained in step 2, and continue stirring; Step 4: In a temperature-controlled box, add the remaining pH regulator to the solution obtained in step 3 until the pH value is 5.5-6.8, and continue stirring until the electrolyte is prepared.
5. The method for preparing an electrolyte for electrochemical forming of amorphous alloy materials according to claim 4, characterized in that: In the step 1, the temperature of the temperature control box is 30-50° C., the stirring rate is 120-180 r / min, the time is 5-10 min, and ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 150-200 KHz.
6. The method for preparing an electrolyte for electrochemical forming of amorphous alloy materials according to claim 4, characterized in that: In the step 2, the temperature of the temperature control box is 25-30° C., the stirring rate is 100-120 r / min, and the time is 5-10 min. At the same time, ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 100-150 KHz.
7. The method for preparing an electrolyte for electrochemical forming of amorphous alloy materials according to claim 4, characterized in that: In the step 3, the temperature of the temperature control box is 20-25° C., the stirring rate is 60-100 r / min, and the time is 5-10 min. At the same time, ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 80-100 KHz.
8. The method for preparing an electrolyte for electrochemical forming of amorphous alloy materials according to claim 4, characterized in that: In the step 4, the temperature of the temperature control box is 20° C., the stirring rate is 30-60 r / min, and the time is 5-10 min. At the same time, ultrasonic coupling vibration is used to accelerate the mixing of the solution, and the vibration frequency is 80-100 KHz.
9. The method for preparing an electrolyte for electrochemical forming of amorphous alloy materials according to claim 4, characterized in that: In step 4, after the electrolyte is prepared, under the working condition of 20° C., the conductivity of the electrolyte must be controlled to be 5-50 mS / cm before it can be put into electrochemical forming processing.
Citation Information
Patent Citations
Electrolytes for electrochemical machining and electrochemical machining methods using the same electrolyte
CN105081487B
Method for polishing inner surface of nickel capillary tube
CN104451853A
Electrolyte for micro-electrolytic machining of metal glass
CN107322113A
Electrolysis of halide-containing solutions with amorphous metal alloys
CN86105605A